(untitled) (PERcursos Linguísticos, 2022)
This article focus on the treatment agreed to anthroponyms and toponyms in two translations of Esaú e Jacó (1904), a novel by Machado de Assis: in French (performed by Françoise Duprat) and in US-American English (performed by Elizabeth Lowe). Dating back to the works of Cicero (106 BC – 43 BC), translation practice has been analyzed and discussed by translators and/or translation theorists (linguists, philosophers, psychoanalysts, etc.): from the translation act to the questioning about the [im]possibility of the translation itself. Although such points seem to have been overcome in terms of theoretical discussion, it is necessary, however, to allude to known difficulties of translation and, within the scope of those that are contained in a vast list, the difficulties associated with socio-historical and cultural issues are highlighted. This article is focused particularly in anthroponyms (names of people) and toponyms (names of places). The genesis of this work lies in the current questions: should proper names be translated? How do translators behave when translating this class of names? What motivations lead a translator to translate or not a proper name? To encourage this discussion, this article will carry out a case study, preceded by some questions inherent to discussions in translation theory.